IMPLEMENTATION OF SYSTEMATIC CADASTRE IN SECTOR 60 OF THE VALEA LARGĂ COMMUNE, MUREŞ COUNTY, ROMANIA (PANGEEA, 2025)
The systematic registration of all the property in Romania is a priority of the Romanian Government as the implementation of the National Cadastre and Land Registration Programme is vital to our country’s economic development. The registration of property into the integrated system of cadastre and land registration through simplified procedures of systematic registration, as well as the increase in the number of registered property are all objectives assumed by Romania, taking into account the constitutional principle of ownership guarantee.
Keywords: systematic cadastre; Valea Largă; identification; measurement; description; registration